POLA REPRODUKSI PADA SALAK BALI (SA/ACCA ZA/ACCA VAR. AMBOINENSIS (BECC.) MOGEA - KRISWIYANTI, ENIEK; MUKSIN, I KETUT; WATINIASIH, LUH; SUARTINI, MADE (Jurnal Biologi Udayana, 2008)
Research on reproduction patterns of Balinese snake skin fruits (Salak Bali) has been conducted by identifying the availability of pollens on anthers of male and hermaphrodite flowers, the viability of pollens in the pistillum and the present of embryo(s) in the ovulum. Flower samples were collected from Sibetan and Muncan Villages, Karangasem regency. Sample preparations and identifications were conducted in "Stuktur dan Perkembangan Tumbuhan Laboratory" Department of Bilogy, FMIPA Udayana University. The results showed that the pollen has a single apperture, unisulcus, minuta, oblat sferoidal type. The length of polar axis was 15-24 jam (P) and equatorial diameter of 16-24 |im (E). Therefore, the P/E index was 0.99-1.0. The pollen viability before and after anthesis of hermaphrodite flowers was low (71.4% and 50.6% respectively), with very low pollen tube germinations (0.08% of before and 0.48% after anthesis). Similarly, on the anthers of male flowers, the viability of pollens before anthesis was low (75.7%) with pollen germination of 0.18%, and event lower in after anthesis flowers (28.8%) with 0.29% pollen tube germination. Squashed stigma before and after anthesis and 2 days after flowers were opened showed that there was no germination occurred. Therefore, there was no germination in the pistillum, but the embryo developed before flower anthesis, indicates that the reproduction pattern of Salak Bali occurred without fertilizations (agamospermy).
Keywords: Aperture; unisulcus; minuta; oblat sferoidal; Pollen viability; agamospermy